Willingness of Jordanians to shop for grocery online. (2017) - Alawamleh, Mohammad; Ismail, Loiy Bani; Hammad, Dana
This research aims to uncover the range of beliefs held by Jordanian consumers to either use or not use the internet for grocery shopping. Both quantitative and qualitative data were collected. The findings of this study indicate that consumers are not willing to sacrifice price, quality and range of products in exchange for the convenience online shopping affords. The majority of the questionnaire participants expressed that grocery shopping is part of their lifestyle, and that they prefer choosing their own products at sight. Both interviewed parties expressed their point of views from their knowledge and experience of the market, and they strongly emphasised that Jordanians prefer the traditional shopping method and experience. The results indicated that regardless of age, gender, educational level and occupational status, individuals are not keen to switch their shopping routine for reasons mainly related to habitual behaviour and traditions.